UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR IPS SISWA KELAS VII B SMP NEGERI 1 KASIHAN DENGAN MEDIA PEMBELAJARAN VA & AV - MARIA ENI YULIANTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The objectives of this study are (1) efforts to increase interest in social studies learning for class VII B students of SMP Negeri 1 Kasihan (2) efforts to improve social studies learning outcomes for class VIIB students of SMP Negeri 1 Kasihan by using VA & AV learning media. The research was conducted in January – June 2022 in class VIIB with 31 students. This research is a classroom action research with Elliott's cycle model which is carried out in two cycles. One cycle consists of an action plan, implementation/implementation of actions, observations, and reflections on actions. The data were obtained from observations, questionnaires, and interviews with several students, as well as evaluations/tests at the end of the cycle. The results of the CAR show: (1) VA & AV learning media can increase interest in social studies learning for class VIIB students with the results in the pre-cycle there are 11 students out of 31 students or 35.48%, the first cycle increased to 15 students or 48.39% and in the first cycle there were 15 students or 48.39%. II increased to 27 students or 87.10%; (2) VA & AV learning media can improve social studies learning outcomes for class VIIB students with an average test score before learning (pre-cycle) of 67 and after taking action in learning in the first cycle of 73 and in the second cycle of 79. Classically the social studies learning mastery of VIIB students experienced an increase in the pre-cycle of 48.39%, the first cycle of 70.97%, and the second cycle of 90.32%. ABSTRAKTujuan dari penelitian ini adalah (1) upaya untuk meningkatkan minat belajar IPS siswa kelas VII B SMP Negeri 1 Kasihan (2) upaya untuk meningkatkan hasil belajar IPS siswa kelas VIIB SMP Negeri 1 Kasihan dengan menggunakan media pembelajaran VA & AV. Penelitian dilaksanakan pada bulan Januari – Juni 2022 di kelas VIIB dengan jumlah siswa 31 orang. Penelitian ini merupakan penelitian tindakan kelas dengan model siklus dari Elliot yang dilaksanakan dua siklus. Dalam satu siklus terdiri dari rencana tindakan, implementasi/pelaksanaan tindakan, observasi, dan refleksi tindakan. Perolehan data didapat dari observasi , pembagian angket, dan wawancara yang dilakukan terhadap beberapa siswa, serta evaluasi/tes pada akhir siklus. Hasil PTK menunjukkan : (1) media pembelajaran VA & AV dapat meningkatkan minat belajar IPS siswa kelas VIIB dengan hasil pada prasiklus ada 11 siswa dari 31 siswa atau 35,48%, siklus I bertambah menjadi 15 siswa atau 48,39% dan pada siklus II bertambah menjadi 27 siswa atau 87,10% ;(2) media pembelajaran VA & AV dapat meningkatkan hasil belajar IPS siswa kelas VIIB dengan rata-rata nilai test sebelum pembelajaran (prasiklus) sebesar 67 dan setelah dilakukan tindakan dalam pembelajaran pada siklus I sebesar 73 dan pada siklus II sebesar 79. Secara klasikal ketuntasan belajar IPS siswa VIIB mengalami peningkatan/kenaikan yaitu pada prasiklus 48,39%, siklus I sebesar 70,97%, siklus II sebesar 90,32%.